Questions children ask implications for science instruction - Santos, Lea O. (1978)
This paper sought to determine the questions children ask and its implications to science instruction. Conversation interviews and interactions in Filipino among the subjects while the different stimuli were presented to the children were recorded on tape and on paper. Three groups of thirty (30) pupils chosen by cluster sampling in elementary school in Manila were the subjects. Since the main objective of the study was questions, only the questions were analyzed in detail. The type of questions asked was significantly related to both age and sex. Certain question types predominate at certain grade levels.